Yttrium hydride composite shielding material precursor and its manufacturing method and application
By preparing the precursor of yttrium hydride composite shielding material, and using vacuum smelting, hot pressing and other processes, the problem of existing neutron shielding materials being easily contaminated under neutron radiation is solved, and the efficient preparation of yttrium hydride composite materials with good neutron shielding performance is achieved, which is suitable for high-temperature applications such as small mobile reactors.
Patent Information
- Application Number
- CN202411505997.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-10-28
AI Technical Summary
Existing neutron shielding materials are prone to radiocontamination under the action of neutron radiation, resulting in an increase in radioactive waste that requires additional shielding and treatment. The application of yttrium hydride as a neutron shielding material is subject to its difficulty in preparing.
A precursor manufacturing method for yttrium hydride composite shielding material is provided. By providing precursor raw materials, including Ti, C and Y, vacuum smelting and casting, followed by hot pressing, hot forging and cold rolling processing, and finally annealing treatment, yttrium hydride composite shielding material with good neutron shielding properties is prepared.
This method can efficiently prepare yttrium hydride composite shielding material with a certain volume, with good neutron shielding effect, high temperature resistance, lightweight and low induced radioactivity, and is suitable for complex high-temperature application scenarios such as small mobile reactors.
Smart Images

Figure CN119020652B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nuclear power, and specifically relates to an yttrium hydride composite shielding material precursor and a manufacturing method and application thereof. Background Art
[0002] Neutron rays are one of the radioactive effects generated during the operation of the reactor. In order to avoid harm to the personnel and environment around the reactor, the neutron rays generated in the reactor need to be shielded. Common metal materials such as Co, Cr, Ni, Zr, W and other elements are easily activated under neutron irradiation, resulting in radioactive pollution and an increase in radioactive waste that requires additional shielding and treatment. Yttrium hydride has a good absorption capacity for fast neutrons and has good application prospects as a neutron shielding material. However, yttrium hydride itself is difficult to prepare, which limits the application of yttrium hydride as a shielding material. Therefore, a method for manufacturing an yttrium hydride composite shielding material precursor that can be used to efficiently produce yttrium hydride is of positive significance for improving the safety of neutron shielding facilities. Summary of the invention
[0003] The purpose of the present invention is to provide a method for manufacturing a yttrium hydride composite shielding material precursor to improve the manufacturing efficiency of yttrium hydride. The present invention also provides a yttrium hydride composite shielding material precursor, and a yttrium hydride composite shielding material and a method for manufacturing the same.
[0004] According to an embodiment of one aspect of the present invention, a method for manufacturing a yttrium hydride composite shielding material precursor is provided, the method comprising the following steps:
[0005] Step a): Providing a precursor material, wherein the precursor material comprises, by weight, 0.5%-15.0% Ti, 0.15%-4.0% C, and the remainder Y and unavoidable impurities, wherein 3.5≤Ti / C≤4.0;
[0006] Step b): vacuum melting the precursor raw material and casting to obtain an alloy ingot;
[0007] Step c): deforming and annealing the alloy ingot to obtain a yttrium hydride composite shielding material precursor.
[0008] Furthermore, in some embodiments, in the step a), the precursor material further comprises Dy in an amount not exceeding 15% by weight.
[0009] Furthermore, in some embodiments, in the step a), in the precursor raw material, C is added in the form of carbon powder, and the metal component is added in the form of pure metal ingots.
[0010] Furthermore, in some embodiments, in step b), the vacuum melting method is: evacuating to 3×10 -3 Pa, using argon as a protective gas, the precursor raw material is heated to 1600° C.-1800° C. and kept warm for at least 10 minutes.
[0011] Furthermore, in some embodiments, in the step c), the deformation process includes hot pressing and / or hot forging, and also includes cold rolling; wherein the hot pressing and / or hot forging are performed under a protective cover, and the hot pressing temperature is not lower than 800°C, and the hot forging temperature is not lower than 850°C, and the hot pressing and / or hot forging are performed at least three times.
[0012] Furthermore, in some embodiments, in the step c), the annealing treatment is performed at a temperature of 850° C.-950° C., and the holding time is not less than 12 hours.
[0013] According to another embodiment of the present invention, there is provided a yttrium hydride composite shielding material precursor, which is manufactured using the yttrium hydride composite shielding material precursor manufacturing method provided in any of the aforementioned embodiments.
[0014] Furthermore, in some embodiments, the matrix of the yttrium hydride composite shielding material precursor is a Y solid solution in which TiC second phase particles are evenly distributed, and the average grain size of the Y solid solution is 40 μm-100 μm, and the hardness is 90 HV-150 HV.
[0015] According to an embodiment of another aspect of the present invention, a method for manufacturing an yttrium hydride composite shielding material is provided, the method using the yttrium hydride composite shielding material precursor provided in any of the aforementioned embodiments as a raw material, and comprising the following steps: loading the yttrium hydride composite shielding material precursor into a hydrogenation furnace, heating it to 850°C-950°C under a hydrogen pressure of 700Pa-900Pa for at least 6 hours, then cooling it to 700°C at a rate not exceeding 10°C / h, and then continuing to cool to room temperature to obtain a finished yttrium hydride composite shielding material.
[0016] According to an embodiment of still another aspect of the present invention, a yttrium hydride composite shielding material is provided. The yttrium hydride composite shielding material is manufactured using the yttrium hydride composite shielding material manufacturing method provided in the above embodiment. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a metallographic photograph of the yttrium hydride composite shielding material precursor in the first embodiment;
[0018] Figure 2 This is a metallographic photograph of the yttrium hydride composite shielding material precursor in the second embodiment;
[0019] Figure 3This is a metallographic photograph of the yttrium hydride composite shielding material precursor in the third embodiment;
[0020] Figure 4 This is a metallographic photograph of the yttrium hydride composite shielding material precursor in the fourth embodiment;
[0021] Figure 5 This is a metallographic photograph of the yttrium hydride composite shielding material precursor in the sixth embodiment;
[0022] Figure 6 This is a metallographic photograph of the yttrium hydride composite shielding material precursor in the seventh embodiment;
[0023] Figure 7 It is a comparison diagram of thermal neutron fluence rates of different embodiments under thermal neutron source;
[0024] Figure 8 A comparison chart of neutron dose rates in different embodiments under a thermal neutron source.
[0025] The purpose of the above drawings is to explain the present invention in detail so that those skilled in the art can understand the technical concept of the present invention, but it is not intended to limit the present invention. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings.
[0027] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The phrase appearing in various locations in the specification does not necessarily refer to the same embodiment, nor is it limited to mutually exclusive independent or alternative embodiments. Those skilled in the art should be able to understand that the embodiments herein may be combined with other embodiments without causing structural conflicts.
[0028] In the description of this article, the terms "first", "second" and the like are only used to distinguish different objects, and cannot be understood as indicating relative importance or limiting the quantity, specific order or primary and secondary relationship of the described technical features. In the description of this article, the meaning of "plurality" is at least two.
[0029] With the rapid development of small mobile reactor technology, the requirements for the performance of neutron shielding materials are becoming increasingly higher for safety reasons. The performance of existing neutron shielding materials has gradually failed to meet the development requirements of current reactor technology. Radiation shielding materials with high temperature resistance, high shielding efficiency and low induced radioactivity have become an urgent need for the development of commercial reactors. At present, the operating temperature of commonly used polymer composite shielding materials does not exceed 800°C, but with the development of technology, the core temperature of small reactors continues to increase, exceeding the service temperature of existing neutron shielding materials. Compared with polymer composite shielding materials, yttrium hydride has better thermal stability and a decomposition temperature of more than 1000°C, and has good application prospects. However, there are currently process difficulties in the manufacture of large volumes of yttrium hydride, which limits the application of yttrium hydride as a neutron shielding material.
[0030] In order to solve the above problems, an embodiment of one aspect of the present invention provides a method for manufacturing a precursor of an yttrium hydride composite shielding material. First, an yttrium-based alloy precursor is manufactured as a raw material, and then the precursor is hydrogenated, so that an yttrium hydride composite shielding material with a certain volume can be efficiently prepared.
[0031] The method comprises the following steps:
[0032] Step a): Provide a precursor raw material, which includes 0.5%-15.0% Ti, 0.15%-4.0% C by weight, and the balance is Y and inevitable impurities, wherein 3.5≤Ti / C≤4.0, and in a preferred embodiment, also includes no more than 15% Dy. C is added in the form of carbon powder, and the metal component is added in the form of pure metal ingots. Ti and C can form TiC particles during the smelting process, which play a role in refining grains and increasing the hardness of the structure during the solidification process of the Y alloy matrix. When the Ti and C content is too high, the hardness of the finished product will be too high; and when the ratio of Ti to C exceeds the range of 3.5-4.0, the remaining Ti or C will be dissolved in the Y matrix, resulting in easy cracking during the subsequent hydrogenation process.
[0033] Step b): Vacuum melt the raw materials and evacuate the vacuum furnace to 3×10 -3 Pa, introduce argon as protective gas, heat the precursor raw material to 1600-1800°C (1700°C in a preferred embodiment) and keep it warm for at least 10 minutes to obtain a uniformly mixed metal melt. Cast the metal melt into an alloy ingot.
[0034] Step c): The alloy ingot is subjected to hot pressing and / or hot forging, and then cold rolling. The hot pressing and hot forging are both carried out in a protective sleeve to prevent the alloy from oxidation. The processing temperature of hot deformation is not less than 800°C, and the hot forging temperature is not less than 850°C. The hot pressing and / or hot forging are performed at least three times to fully break up the dendrites formed during the solidification process, eliminate casting defects such as pinholes and looseness, and improve the uniformity of the alloy matrix structure. The cold rolling process is performed at least three times, and after the cold rolling is completed, an annealing treatment is performed at 850°C-900°C (900°C in the preferred embodiment) for 12 hours to obtain an yttrium hydride composite shielding material precursor.
[0035] The yttrium hydride composite shielding material precursor manufactured by the above method has an alloy tissue matrix of Y solid solution, in which TiC particles are evenly distributed, and the TiC particles are polygonal or elliptical. The melting point of TiC particles is very high, and they can play a role in refining grains during the solidification process of the Y alloy matrix. At the same time, the TiC distributed in the organization can increase the hardness of the precursor material and improve its wear resistance. Furthermore, the Ti element is a low-activation element, and the induced radioactivity is weak after neutron irradiation, which helps to simplify the shielding design and improve the safety of the system, and reduce the processing pressure of radioactive waste. In a preferred embodiment, the added Dy can be dissolved in the Y alloy matrix, and the Dy element has good neutron absorption ability, and the equivalent neutron absorption cross section can reach 1100 barn, which can effectively enhance the shielding effect.
[0036] In the yttrium hydride composite shielding material precursor, the average grain size of the Y solid solution matrix is 40 μm-100 μm, and the hardness is 90 HV-150 HV.
[0037] The yttrium hydride composite shielding material precursor is subjected to high-temperature hydrogenation treatment to obtain the yttrium hydride composite shielding material. The specific process is as follows: the yttrium hydride composite shielding material precursor is loaded into a hydrogenation furnace, heated to 850°C-950°C (900°C in a preferred embodiment), and hydrogenated for 6 hours under a hydrogen pressure of 700Pa-900Pa (800Pa in a preferred embodiment), then slowly cooled to 700°C at a rate not exceeding 10°C / h, and then cooled to room temperature, and the finished yttrium hydride composite shielding material is obtained by taking out the furnace. The method has a simple production process and high production efficiency. Due to the presence of TiC particles in the yttrium hydride composite shielding material precursor, the alloy matrix grains are refined, and cracking and other defects are not likely to occur during the hydrogenation process. A yttrium hydride composite shielding material with a certain volume can be formed, which is more conducive to the large-scale manufacture of shielding structures in reactors. At the same time, the TiC particles themselves have low induced radioactivity, which can simplify the shielding design and the difficulty of waste treatment is relatively low. The yttrium hydride composite shielding material prepared by the method can serve for a long time in a high temperature environment above 800°C and has a good neutron shielding effect. Furthermore, TiC has high hardness, and TiC particles can further improve the wear resistance of the yttrium hydride composite shielding material, thereby improving the reliability and service life of the neutron shielding structure.
[0038] In the first embodiment, a method for manufacturing a yttrium hydride composite shielding material precursor is as follows:
[0039] Raw materials are provided, wherein the raw materials have a weight ratio of Ti 0.5%, C 0.15%, and Y balance, and vacuum melting and casting are performed to obtain alloy ingots. The alloy ingots are subjected to three passes of hot pressing and hot rolling, followed by three passes of cold rolling, and finally annealing.
[0040] The structure of the yttrium hydride composite shielding material precursor is as follows: Figure 1 As shown, the average grain size of the Y solid solution matrix is about 100 μm and the measured hardness is 90 HV.
[0041] The yttrium hydride composite shielding material precursor is subjected to high temperature hydrogenation treatment to obtain a complete, crack-free yttrium hydride composite shielding material block.
[0042] In a second embodiment, a method for manufacturing a yttrium hydride composite shielding material precursor is as follows:
[0043] Raw materials are provided, wherein the raw materials have a weight ratio of Ti 2.0%, C 0.5%, and Y balance, and vacuum melting and casting are performed to obtain alloy ingots. The alloy ingots are subjected to three passes of hot pressing and hot rolling, followed by three passes of cold rolling, and finally annealing.
[0044] The structure of the yttrium hydride composite shielding material precursor is as follows: Figure 2As shown, the average grain size of the Y solid solution matrix is about 80μm and the measured hardness is 98HV.
[0045] The yttrium hydride composite shielding material precursor is subjected to high temperature hydrogenation treatment to obtain a complete, crack-free yttrium hydride composite shielding material block.
[0046] In a third embodiment, a method for manufacturing a yttrium hydride composite shielding material precursor is as follows:
[0047] Raw materials are provided, wherein the raw materials have a weight ratio of Ti 5.0%, C 1.3%, and Y balance, and vacuum melting and casting are performed to obtain alloy ingots. The alloy ingots are subjected to three passes of hot pressing and hot rolling, followed by three passes of cold rolling, and finally annealing.
[0048] The structure of the yttrium hydride composite shielding material precursor is as follows: Figure 3 As shown, the average grain size of the Y solid solution matrix is about 60μm and the measured hardness is 116HV.
[0049] The yttrium hydride composite shielding material precursor is subjected to high temperature hydrogenation treatment to obtain a complete, crack-free yttrium hydride composite shielding material block.
[0050] In a fourth embodiment, a method for manufacturing a yttrium hydride composite shielding material precursor is as follows:
[0051] Raw materials are provided, wherein the raw materials have a weight ratio of Ti 8.0%, C 2.0%, and Y balance, and vacuum melting and casting are performed to obtain alloy ingots. The alloy ingots are subjected to three passes of hot pressing and hot rolling, followed by three passes of cold rolling, and finally annealing.
[0052] The structure of the yttrium hydride composite shielding material precursor is as follows: Figure 4 As shown, the average grain size of the Y solid solution matrix is about 40μm-50μm, and the measured hardness is 127HV.
[0053] The yttrium hydride composite shielding material precursor is subjected to high temperature hydrogenation treatment to obtain a complete, crack-free yttrium hydride composite shielding material block.
[0054] In a fifth embodiment, a method for manufacturing a yttrium hydride composite shielding material precursor is as follows:
[0055] Raw materials are provided, wherein the raw materials have a weight ratio of Ti 10.0%, C 2.5%, and Y balance, and vacuum melting and casting are performed to obtain alloy ingots. The alloy ingots are subjected to three passes of hot pressing and hot rolling, followed by three passes of cold rolling, and finally annealing.
[0056] The average grain size of the Y solid solution matrix in the structure of the yttrium hydride composite shielding material precursor is about 40μm-50μm, and the hardness is measured to be 134HV.
[0057] The yttrium hydride composite shielding material precursor is subjected to high temperature hydrogenation treatment to obtain a complete, crack-free yttrium hydride composite shielding material block.
[0058] In a sixth embodiment, a method for manufacturing a yttrium hydride composite shielding material precursor is as follows:
[0059] Raw materials are provided, wherein the raw materials have a weight ratio of Ti 15.0%, C 4.0%, and Y balance, and vacuum melting and casting are performed to obtain alloy ingots. The alloy ingots are subjected to three passes of hot pressing and hot rolling, followed by three passes of cold rolling, and finally annealing.
[0060] The structure of the yttrium hydride composite shielding material precursor is as follows: Figure 5 As shown, the average grain size of the Y solid solution matrix is about 30μm-40μm, and the measured hardness is 146HV.
[0061] The yttrium hydride composite shielding material precursor is subjected to high temperature hydrogenation treatment to obtain a complete, crack-free yttrium hydride composite shielding material block.
[0062] In the seventh embodiment, a method for manufacturing a yttrium hydride composite shielding material precursor is as follows:
[0063] Raw materials are provided, wherein the raw materials have a weight ratio of Ti 5.0%, C 1.3%, Dy 15%, and Y balance, and vacuum melting and casting are performed to obtain alloy ingots. The alloy ingots are subjected to three passes of hot pressing and hot rolling, followed by three passes of cold rolling, and finally annealing.
[0064] The structure of the yttrium hydride composite shielding material precursor is as follows: Figure 6 As shown, the average grain size of the Y solid solution matrix is 50 μm and the measured hardness is 119 HV.
[0065] The yttrium hydride composite shielding material precursor is subjected to high temperature hydrogenation treatment to obtain a complete, crack-free yttrium hydride composite shielding material block.
[0066] In an eighth embodiment, a method for manufacturing a yttrium hydride composite shielding material precursor is as follows:
[0067] Raw materials are provided, wherein the raw materials have a weight ratio of Ti 5.0%, C 1.3%, Dy 10%, and Y balance, and vacuum melting and casting are performed to obtain alloy ingots. The alloy ingots are subjected to three passes of hot pressing and hot rolling, followed by three passes of cold rolling, and finally annealing.
[0068] The structure of the yttrium hydride composite shielding material precursor is as follows: Figure 4 As shown, the average grain size of the Y solid solution matrix is 50μm-60μm, and the measured hardness is 125HV.
[0069] The yttrium hydride composite shielding material precursor is subjected to high temperature hydrogenation treatment to obtain a complete, crack-free yttrium hydride composite shielding material block.
[0070] The yttrium hydride composite shielding material provided in the above embodiment has the advantages of fine grains, good strength and toughness, high temperature resistance, light weight, low induced radioactivity and high shielding efficiency, and is suitable for complex high-temperature application scenarios such as small mobile reactors.
[0071] Taking a thermal neutron source with an average energy of 0.023 MeV as the simulation object, the thermal neutron flux rate on the surface of the shielding material (the third embodiment and the seventh embodiment) in the unshielded state and after being shielded by a 10 cm thick shielding material is as follows: Figure 7 It can be seen that compared with the unshielded state, the thermal neutron flux rate is reduced by more than one order of magnitude after being shielded by the yttrium hydride composite shielding material provided in the third embodiment (YH-5Ti-1.3C); and compared with the unshielded state, the thermal neutron flux rate is reduced by more than three orders of magnitude after being shielded by the yttrium hydride composite shielding material provided in the seventh embodiment (YH-5Ti-1.3C-15.0Dy).
[0072] Under the same neutron source, the neutron dose rates on the shielding material surface in the unshielded state, the shielding in the third embodiment, and the shielding in the seventh embodiment are as follows: Figure 8 As shown, it can be seen that the neutron dose rate is significantly reduced after shielding by the yttrium hydride composite shielding material provided in the embodiment.
[0073] The purpose of the above embodiments is to further explain the present invention in detail in conjunction with the accompanying drawings so that those skilled in the art can understand the technical concept of the present invention. Within the scope of the present invention, the optimization or equivalent replacement of the components or method steps involved, and the combination of implementation methods in different embodiments without conflict of structure and principle, all fall within the protection scope of the present invention.
Claims
1. A method for manufacturing a precursor of a yttrium hydride composite shielding material, characterized in that: The following steps are involved: Step a): Providing a precursor material, wherein the precursor material comprises, by weight, 0.5%-15.0% Ti, 0.15%-4.0% C, and the remainder Y and unavoidable impurities, wherein 3.5≤Ti / C≤4.0; Step b): vacuum melting the precursor raw material and casting to obtain an alloy ingot; Step c): deforming and annealing the alloy ingot to obtain a yttrium hydride composite shielding material precursor; The deformation process includes hot pressing and / or hot forging, and also includes cold rolling; wherein the hot pressing and / or hot forging are performed under a protective cover, and the hot pressing temperature is not less than 800°C, and the hot forging temperature is not less than 850°C, and the hot pressing and / or hot forging are performed at least three times; The annealing treatment is performed at a temperature of 850°C-950°C and the holding time is not less than 12 hours; The prepared yttrium hydride composite shielding material precursor comprises a Y solid solution and TiC second phase particles. The average grain size of the Y solid solution is 40 μm-100 μm, and the hardness is 90 HV-150 HV.
2. The method for manufacturing a precursor of a yttrium hydride composite shielding material according to claim 1, characterized in that: In the step a), the precursor material further comprises Dy in an amount not exceeding 15% by weight.
3. The method for manufacturing a precursor of a yttrium hydride composite shielding material according to claim 1 or 2, characterized in that: In the step a), in the precursor raw material, C is added in the form of carbon powder, and the metal component is added in the form of pure metal ingots.
4. The method for manufacturing a precursor of a yttrium hydride composite shielding material according to claim 1 or 2, characterized in that: In the step b), the vacuum melting method is: evacuating to 3×10 -3 Pa, using argon as a protective gas, the precursor raw material is heated to 1600° C.-1800° C. and kept warm for at least 10 minutes.
5. A yttrium hydride composite shielding material precursor, characterized in that: The yttrium hydride composite shielding material precursor is manufactured by the method for manufacturing a yttrium hydride composite shielding material precursor according to any one of claims 1 to 4.
6. The yttrium hydride composite shielding material precursor according to claim 5, characterized in that: The matrix of the yttrium hydride composite shielding material precursor is a Y solid solution in which TiC second phase particles are evenly distributed. The average grain size of the Y solid solution is 40 μm-100 μm, and the hardness is 90 HV-150 HV.
7. A method for manufacturing a yttrium hydride composite shielding material, characterized in that: The yttrium hydride composite shielding material precursor as claimed in claim 5 or 6 is used as a raw material, and the following steps are included: The yttrium hydride composite shielding material precursor is loaded into a hydrogenation furnace, heated to 850°C-950°C under a hydrogen pressure of 700Pa-900Pa for at least 6 hours, then cooled to 700°C at a rate not exceeding 10°C / h, and then continued to cool to room temperature to obtain a finished yttrium hydride composite shielding material.
8. A yttrium hydride composite shielding material, characterized in that: The yttrium hydride composite shielding material is manufactured using the manufacturing method of claim 7.
Citation Information
Patent Citations
High-temperature-resistant and hydrogen-induced cracking-resistant yttrium-based alloy material for neutron shielding as well as preparation method and application thereof
CN115652164A
Yttrium hydride moderated material as well as preparation method and application thereof
CN116253290A
High-temperature-resistant yttrium-silicon alloy material for nuclear shielding as well as preparation method and application thereof
CN117965987A